2004
DOI: 10.1111/j.1365-2958.2004.04410.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characterization of Saccharomyces cerevisiae kha1 deletion mutants

Abstract: Summary Maintenance of intracellular K+ homeostasis is one of the crucial requisites for the survival of yeast cells. In Saccharomyces cerevisiae , the high K + content corresponds to a steady state between simultaneous influx and efflux across the plasma membrane. One of the transporters formerly believed to extrude K + from the yeast cells (besides Ena1-4p and Nha1p) was named Kha1p and presumed as a putative plasma membrane K + /H + antiporter. We prepared kha1 and tok1-kha1 deletion strains in the B31 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 55 publications
6
111
0
Order By: Relevance
“…[17][18][19] As expected, the host strain AXT3 transformed with the empty vector is unable to grow at 100 mM extracellular Na ϩ , at both extracellular pH of 4.0 and 7.4 ( Figure 7A). Expression of prevacuolar (Nhx1) and plasmalemmal (Nha1) S. cerevisiae NHE and human NHA2 all rescue the salt-sensitive phenotype at pH 4 but not at pH 7.4.…”
Section: Resultsmentioning
confidence: 84%
“…[17][18][19] As expected, the host strain AXT3 transformed with the empty vector is unable to grow at 100 mM extracellular Na ϩ , at both extracellular pH of 4.0 and 7.4 ( Figure 7A). Expression of prevacuolar (Nhx1) and plasmalemmal (Nha1) S. cerevisiae NHE and human NHA2 all rescue the salt-sensitive phenotype at pH 4 but not at pH 7.4.…”
Section: Resultsmentioning
confidence: 84%
“…A pre-vacuolar-bound Na ϩ /H ϩ antiporter (Nhx1p) mediates cation/H ϩ exchange in prevacuoles and possibly in other intracellular compartments (12,16). More recently, a K ϩ /H ϩ exchanger (Kha1p) at the Golgi was reported, and its role in pH regulation was postulated (10,11). Although in S. cerevisiae, vacuolar Na ϩ (and K ϩ ) transport has been attributed mainly to Nhx1p (14), our data and other reports (18,19) Our results clearly indicated that Vnx1 mediated Na ϩ , K ϩ , and Li ϩ transport into the vacuole and that the lack of Vnx1p increased the salt sensitivity of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two other Nha1p homologues, Kha1p and Nhx1p, have been identified in S. cerevisiae. Kha1p has been described as a putative K ϩ /H ϩ antiporter, and its deletion induced a growth defect at high external pH and hygromycin (10). Kha1p co-localized with Mntp1p, a Golgi-specific marker (11).…”
mentioning
confidence: 99%
“…Yeast mutants with disrupted kha1 gene alone exhibited no obvious phenotype (Maresova and Sychrova, 2005), so we expressed CHX20 in a yeast mutant (KTA40-2). This strain lacks functional vacuolar and PM-localized Na…”
Section: Function Of Atchx20 In Yeastmentioning
confidence: 99%
“…1 antiporters, PM Na 1 pumps (Dnhx1 Dnha1 and Dena1-4), as well as the putative K 1 /H 1 exchanger (Dkha1; Maresova and Sychrova, 2005). Strain KTA40-2 is highly sensitive to salt and to high K 1 , so the transformant (KTA40-2-CHX20) was tested for its ability to grow on moderate levels of Na 1 and very high K…”
Section: /Hmentioning
confidence: 99%